Transferring the international DRR policy into the local context - EKİN ERKAN, NİHAL (SPRINGER, 2013)
The disaster experiences of the past resulted in the need for a new international policy. The paper examines the transfer of the international policy for disaster risk reduction (DRR) into a local context, Turkey and Turkish, where new and old perspectives meet. Analyzed is a corpus consisting of two texts, with the purpose of examining the concepts' actual use and contexts shaped by different attitudes, based on the three-dimensional framework of critical discourse analysis, translation studies and conceptual history. The concept transfer from international to the local level inevitably involves translation. The texts included new DRR terms as a result of the concealed translation attempts to adjust the old and contemporary terminologies. Thus, non-functional terms with blurred meanings arose. The awareness that such processes of transfer are complex would help to overcome this kind of simplistic top-down approaches and to give priority to communicative labor. The framework is not presented due to space limitations. It was also observed that the Turkish terminology lacks clear definitions. To affirm this, an in-depth analysis is needed. Terms transferred across contexts may end lacking conceptualizations due to non-functional translation choices. When adopting new social policies, this can be overcome through making effort for communication. This research looks at conceptual struggles related to social issues from a different aspect. The vague terms and inefficiencies in social implementations can be avoided by authorities being aware that discourse, translation and their production are parts of social action.
Keywords: Disaster risk reduction; Transfer of concepts; Translation studies Urban studies; Critical discourse analysis; Transfer of international policies